90. ∫ 0 π 2 s i n ( x ) 3 c o s ( x ) 3 + s i n ( x ) 3 d x \int_{0}^{\frac{\pi}{2}} \frac{sin(x)^3}{cos(x)^3 + sin(x)^3} dx ∫ 0 2 π c o s ( x ) 3 + s i n ( x ) 3 s i n ( x ) 3 d x
try some.
∫ 0 π 2 s i n ( x ) 3 c o s ( x ) 3 + s i n ( x ) 3 d x c o s 3 x + s i n 3 x = ( c o s 2 x + s i n 2 x ) ( c o s x + s i n x ) − c o s x s i n 2 x − c o s 2 x s i n x = c o s x + s i n x − c o s x s i n 2 x − c o s 2 s i n x = c o s x ( 1 − s i n 2 x ) + s i n x ( 1 − c o s 2 x ) u = c o s ( x ) , d u = − s i n ( x ) d x = ∫ s i n x ( 1 − u 2 ) u 3 + s i n x ( 1 − u 2 ) ( − 1 s i n x ) d u u = c o s 3 x + s i n 3 x , d u / d x = 3 c o s 2 x ( − s i n x ) + 3 s i n 2 x c o s x = ∫ s i n x ( 1 − c o s 2 x ) c o s 3 x + s i n 3 x d x = ∫ 1 c o t 3 x + 1 d x
\begin{aligned}
&\int_0^{\frac{\pi}{2}} \frac{sin(x)^3}{cos(x)^3 + sin(x)^3} dx\\
&cos^3x+sin^3x=(cos^2x+sin^2x)(cosx+sinx)-cosxsin^2x-cos^2xsinx\\
&=cosx+sinx-cosxsin^2x-cos^2sinx\\
&=cosx(1-sin^2x)+sinx(1-cos^2x) \\
& u = cos(x), du=-sin(x)dx\\
&=\int \frac{sinx(1-u^2)}{u^3+sinx(1-u^2)} (-\frac{1}{sinx})du\\
& u=cos^3x+sin^3x, du/dx=3cos^2x(-sinx)+3sin^2xcosx \\
&=\int \frac{sinx(1-cos^2x)}{cos^3x+sin^3x}dx \\
&=\int \frac{1}{cot^3x+1}dx
\end{aligned}
∫ 0 2 π c o s ( x ) 3 + s i n ( x ) 3 s i n ( x ) 3 d x c o s 3 x + s i n 3 x = ( c o s 2 x + s i n 2 x ) ( c o s x + s i n x ) − c o s x s i n 2 x − c o s 2 x s i n x = c o s x + s i n x − c o s x s i n 2 x − c o s 2 s i n x = c o s x ( 1 − s i n 2 x ) + s i n x ( 1 − c o s 2 x ) u = c o s ( x ) , d u = − s i n ( x ) d x = ∫ u 3 + s i n x ( 1 − u 2 ) s i n x ( 1 − u 2 ) ( − s i n x 1 ) d u u = c o s 3 x + s i n 3 x , d u / d x = 3 c o s 2 x ( − s i n x ) + 3 s i n 2 x c o s x = ∫ c o s 3 x + s i n 3 x s i n x ( 1 − c o s 2 x ) d x = ∫ c o t 3 x + 1 1 d x
∫ s i n 3 x c o s 3 x + s i n 3 x d x ( c o s x + s i n x ) 3 = c o s 3 x + s i n 3 x + 3 c o s 2 x s i n x + 3 c o s x s i n 2 x = c o s 3 x + s i n 3 x + 3 c o s x s i n x ( c o s x + s i n x ) = ∫ 1 c o t 3 x + 1 d x = ∫ 1 ( 1 + c o t 2 ) ( c o t x ) − c o t x + 1 d x = ∫ 1 c s c 2 x c o t x − c o t x + 1 d x = ∫ t a n 3 x 1 + t a n 3 x d x ( u = t a n x , d u = s e c 2 x d x ) = ∫ u 3 1 + u 3 1 s e c 2 x d x
\int \frac{sin^3x}{cos^3x+sin^3x} dx\\
(cosx+sinx)^3 = cos^3x+sin^3x+3cos^2xsinx+3cosxsin^2x\\
=cos^3x+sin^3x+3cosxsinx(cosx+sinx)\\
=\int \frac{1}{cot^3x+1}dx=\int \frac{1}{(1+cot^2)(cotx)-cotx+1}dx\\
=\int \frac{1}{csc^2xcotx-cotx+1}dx\\
=\int \frac{tan^3x}{1+tan^3x}dx (u=tan x, du=sec^2x dx)\\
=\int \frac{u^3}{1+u^3}\frac{1}{sec^2x}dx
∫ c o s 3 x + s i n 3 x s i n 3 x d x ( c o s x + s i n x ) 3 = c o s 3 x + s i n 3 x + 3 c o s 2 x s i n x + 3 c o s x s i n 2 x = c o s 3 x + s i n 3 x + 3 c o s x s i n x ( c o s x + s i n x ) = ∫ c o t 3 x + 1 1 d x = ∫ ( 1 + c o t 2 ) ( c o t x ) − c o t x + 1 1 d x = ∫ c s c 2 x c o t x − c o t x + 1 1 d x = ∫ 1 + t a n 3 x t a n 3 x d x ( u = t a n x , d u = s e c 2 x d x ) = ∫ 1 + u 3 u 3 s e c 2 x 1 d x
fail… very hard…
Hint: tan x, x=arctan subs... ∫ s i n 3 x c o s 3 x + s i n 3 x d x = ∫ t a n 3 x 1 + t a n 3 x d x , ( x = t a n − 1 y , d x = 1 1 + y 2 d y ) = ∫ y 3 1 + y 3 1 1 + y 2 d y = ∫ y 3 + 1 − 1 ( 1 + y 2 ) ( 1 + y 3 ) d y = ∫ 1 ( 1 + y 2 ) − ∫ 1 ( 1 + y 2 ) ( 1 + y 3 ) d y = a r c t a n ( y ) − ∫ a y + b 1 + y 2 + c y 2 + d y + e 1 + y 3 d y a + c = 0 , b + d = 0 , c + e = 0 , d + a = 0 , b + e = 1 = a = − c , b = − d , c = − e , d − c = 0 , − c + − c = 1 , c = d = − b = − a , c = d = − ( 1 / 2 ) , a = b = e = ( 1 / 2 ) ( 1 / 2 ) y + ( 1 / 2 ) 1 + y 2 + − ( 1 / 2 ) y 2 + ( − 1 / 2 ) y + ( 1 / 2 ) 1 + y 3 = a r c t a n ( y ) − ∫ ( 1 / 2 ) y + ( 1 / 2 ) 1 + y 2 + − ( 1 / 2 ) y 2 + ( − 1 / 2 ) y + ( 1 / 2 ) 1 + y 3 d y = a r c t a n ( y ) − 1 2 ∫ 1 + y 1 + y 2 d y + 1 2 ∫ y 2 + y − 1 1 + y 3 d y ∫ 1 + y 1 + y 2 d y = ∫ 1 1 + y 2 d y + ∫ y 1 + y 2 d y = a r c t a n ( y ) + 1 2 l n ∣ 1 + y 2 ∣ R = ∫ y 2 + y − 1 1 + y 3 = ∫ y 2 1 + y 3 d y + ∫ y − 1 1 + y 3 d y ∫ y 2 1 + y 3 d y = 1 3 l n ( 1 + y 3 ) y 3 + 1 = ( y + 1 ) ( y 2 − y + 1 ) ∫ y − 1 1 + y 3 d y = ∫ a y + b y 2 − y + 1 + c y + 1 d y a + c = 0 , b − c + a = 0 , b + c = 1 , a = − c , b = 2 c c = 1 / 3 , b = 2 / 3 , a = − 1 / 3 ∫ y − 1 1 + y 3 d y = ∫ ( − 1 / 3 ) y + 2 / 3 y 2 − y + 1 + 1 / 3 y + 1 d y = − 1 3 ∫ y − 2 y 2 − y + 1 d y + 1 3 ∫ 1 y + 1 d y = − 2 3 ∫ y − 1 2 − 3 2 y 2 − y + 1 d y + 1 3 l n ∣ y + 1 ∣ ∫ y − 1 2 − 3 2 y 2 − y + 1 d y = ∫ y − 1 2 y 2 − y + 1 d y − 3 2 ∫ 1 y 2 − y + 1 d y = 1 2 l n ( y 2 − y + 1 ) − 3 2 ∫ 1 y 2 − y + 1 d y ∫ 1 y 2 − y + 1 d y = ∫ 1 t a n 2 x + 1 − t a n x s e c 2 x d x = ∫ s e c 2 x s e c 2 x − t a n x d x = ∫ 1 c o s 2 x 1 − c o s x s i n x c o s 2 x d x = ∫ 1 1 − c o s x s i n x d x = ∫ 2 2 − s i n 2 x d x 1 y 2 − y + 1 = c ( a y + b ) ′ 1 + ( a y + b ) 2 = a c a 2 y 2 + 2 a b y + b 2 + 1 a / c = 1 , 2 b / c = − 1 , ( b 2 + 1 ) / a c = 1 , a = c = − 2 b ( b 2 + 1 ) = ( 4 b 2 ) , 3 b 2 = 1 , b = ± 1 3 b = − 1 3 , a = c = 2 3 1 y 2 − y + 1 = 2 3 2 3 1 + ( 2 3 y − 1 3 ) 2 ∫ 1 y 2 − y + 1 d y = 2 3 ∫ 2 3 1 + ( 2 3 y − 1 3 ) 2 d y = 2 3 a r c t a n ( 2 3 y − 1 3 ) R = ∫ y 2 + y − 1 1 + y 3 d y = 1 3 l n ( 1 + y 3 ) − 2 3 ( 1 2 l n ( y 2 − y + 1 ) − 3 a r c t a n ( 2 3 y − 1 3 ) ) + 1 3 l n ( y + 1 ) R = 2 3 l n ( y + 1 ) + 2 3 a r c t a n ( 2 y − 1 3 ) ∴ Q = a r c t a n ( y ) − 1 2 ∫ 1 + y 1 + y 2 d y + 1 2 ∫ y 2 + y − 1 1 + y 3 d y = a r c t a n ( y ) − 1 2 ( a r c t a n ( y ) + 1 2 l n ∣ 1 + y 2 ∣ ) + 1 2 ( ∫ y 2 + y − 1 1 + y 3 d y ) = 1 2 x − 1 4 l n ∣ 1 + t a n 2 x ∣ + 1 2 R = 1 2 x − 1 4 l n ∣ 1 + t a n 2 x ∣ + 1 3 l n ∣ 1 + t a n x ∣ + 1 3 a r c t a n ( 2 t a n x − 1 3 )
\begin{aligned}
&\text{Hint: tan x, x=arctan subs... }\\
&\int \frac{sin^3x}{cos^3x+sin^3x} dx \\
&=\int \frac{tan^3x}{1+tan^3x}dx, \quad (x=tan^{-1}y, dx=\frac{1}{1+y^2}dy)\\
&=\int \frac{y^3}{1+y^3}\frac{1}{1+y^2}dy \\
&=\int \frac{y^3+1-1}{(1+y^2)(1+y^3)}dy \\
&=\int \frac{1}{(1+y^2)}-\int \frac{1}{(1+y^2)(1+y^3)}dy \\
&=arctan(y)-\int \frac{ay+b}{1+y^2}+\frac{cy^2+dy+e}{1+y^3} dy\\
& a+c=0, b+d=0, c+e=0, d+a=0, b+e=1\\
&=a=-c, b=-d, c=-e, d-c=0, -c+-c=1, c=d=-b=-a, \\
&c=d=-(1/2), a=b=e=(1/2)\\
&\frac{(1/2)y+(1/2)}{1+y^2}+\frac{-(1/2)y^2+(-1/2)y+(1/2)}{1+y^3}\\
&=arctan(y)-\int \frac{(1/2)y+(1/2)}{1+y^2}+\frac{-(1/2)y^2+(-1/2)y+(1/2)}{1+y^3} dy\\
&=arctan(y)-\frac 1 2\int \frac{1+y}{1+y^2}dy+\frac 1 2 \int \frac{y^2+y-1}{1+y^3} dy\\
&\int \frac{1+y}{1+y^2}dy =\int \frac 1 {1+y^2}dy+\int \frac y {1+y^2}dy\\
&=arctan (y)+\frac 1 2 ln|1+y^2|\\
&R=\int \frac{y^2+y-1}{1+y^3}=\int \frac {y^2}{1+y^3}dy+\int \frac {y-1}{1+y^3}dy\\
&\int \frac {y^2}{1+y^3}dy=\frac 1 3 ln(1+y^3)\\
&y^3+1=(y+1)(y^2-y+1)\\
&\int \frac {y-1}{1+y^3}dy=\int \frac{ay+b}{y^2-y+1}+\frac{c}{y+1}dy\\
&a+c=0, b-c+a=0, b+c=1, a=-c, b=2c\\
&c=1/3, b=2/3, a=-1/3\\
&\int \frac {y-1}{1+y^3}dy=\int \frac{(-1/3)y+2/3}{y^2-y+1}+\frac{1/3}{y+1}dy\\
&=-\frac 1 3 \int \frac{y-2}{y^2-y+1}dy+\frac 1 3 \int \frac{1}{y+1}dy\\
&=-\frac 2 3 \int \frac{y-\frac 1 2-\frac 3 2 }{y^2-y+1}dy+\frac 1 3 ln|y+1|\\
&\int \frac{y-\frac 1 2-\frac 3 2 }{y^2-y+1}dy=\int \frac{y-\frac 1 2}{y^2-y+1}dy-\frac 3 2 \int \frac{1}{y^2-y+1}dy \\
&=\frac 1 2 ln(y^2-y+1) -\frac 3 2 \int \frac{1}{y^2-y+1}dy \\
&\int \frac{1}{y^2-y+1}dy=\int \frac {1}{tan^2x+1-tanx}sec^2xdx\\
&=\int \frac {sec^2x}{sec^2x-tanx}dx=\int \frac {\frac 1 {cos^2x}}{\frac{1-cosxsinx}{cos^2x}}dx=\int \frac 1 {1-cosxsinx}dx\\
&=\int \frac{2}{2- sin2x}dx\\
&\frac{1}{y^2-y+1}=c\frac {(ay+b)'}{1+(ay+b)^2}=\frac{ac}{a^2y^2+2aby+b^2+1}\\
&a/c=1, 2b/c=-1, (b^2+1)/ac=1, a=c=-2b\\
&(b^2+1)=(4b^2), 3b^2=1, b=\pm \frac 1 {\sqrt{3}} \\
&b=-\frac 1 {\sqrt 3}, a=c=\frac 2 {\sqrt 3}\\
&\frac{1}{y^2-y+1}=\frac 2 {\sqrt 3}\frac{\frac 2 {\sqrt 3}}{1+(\frac 2 {\sqrt 3}y-\frac 1 {\sqrt 3})^2}\\
&\int \frac{1}{y^2-y+1}dy=\frac 2 {\sqrt 3}\int \frac{\frac 2 {\sqrt 3}}{1+(\frac 2 {\sqrt 3}y-\frac 1 {\sqrt 3})^2} dy\\
&=\frac 2 {\sqrt 3}arctan(\frac 2 {\sqrt 3}y-\frac 1 {\sqrt 3})\\
& R=\int \frac{y^2+y-1}{1+y^3} dy = \frac1 3 ln(1+y^3)-\frac 2 3 ( \frac 1 2 ln(y^2-y+1)-\sqrt 3 arctan(\frac 2 {\sqrt 3} y-\frac 1 {\sqrt 3}) ) +\frac 1 3 ln(y+1)\\
&R=\frac 2 3 ln (y+1)+\frac 2 {\sqrt 3} arctan( \frac{2y-1}{\sqrt 3})\\
& \therefore Q=arctan(y)-\frac 1 2\int \frac{1+y}{1+y^2}dy+\frac 1 2 \int \frac{y^2+y-1}{1+y^3} dy \\
&=arctan(y)-\frac 1 2 ( arctan (y)+\frac 1 2 ln|1+y^2|)\\
&+\frac 1 2 ( \int \frac{y^2+y-1}{1+y^3} dy )\\
&=\frac 1 2 x-\frac 1 4 ln|1+tan^2x|+\frac 1 2 R\\
&=\frac 1 2 x-\frac 1 4 ln|1+tan^2x|+\frac{1}{3}ln|1+tanx|+\frac 1 {\sqrt 3}arctan(\frac {2tanx-1}{\sqrt 3})
\end{aligned}\\
Hint: tan x, x=arctan subs... ∫ c o s 3 x + s i n 3 x s i n 3 x d x = ∫ 1 + t a n 3 x t a n 3 x d x , ( x = t a n − 1 y , d x = 1 + y 2 1 d y ) = ∫ 1 + y 3 y 3 1 + y 2 1 d y = ∫ ( 1 + y 2 ) ( 1 + y 3 ) y 3 + 1 − 1 d y = ∫ ( 1 + y 2 ) 1 − ∫ ( 1 + y 2 ) ( 1 + y 3 ) 1 d y = a r c t a n ( y ) − ∫ 1 + y 2 a y + b + 1 + y 3 c y 2 + d y + e d y a + c = 0 , b + d = 0 , c + e = 0 , d + a = 0 , b + e = 1 = a = − c , b = − d , c = − e , d − c = 0 , − c + − c = 1 , c = d = − b = − a , c = d = − ( 1 / 2 ) , a = b = e = ( 1 / 2 ) 1 + y 2 ( 1 / 2 ) y + ( 1 / 2 ) + 1 + y 3 − ( 1 / 2 ) y 2 + ( − 1 / 2 ) y + ( 1 / 2 ) = a r c t a n ( y ) − ∫ 1 + y 2 ( 1 / 2 ) y + ( 1 / 2 ) + 1 + y 3 − ( 1 / 2 ) y 2 + ( − 1 / 2 ) y + ( 1 / 2 ) d y = a r c t a n ( y ) − 2 1 ∫ 1 + y 2 1 + y d y + 2 1 ∫ 1 + y 3 y 2 + y − 1 d y ∫ 1 + y 2 1 + y d y = ∫ 1 + y 2 1 d y + ∫ 1 + y 2 y d y = a r c t a n ( y ) + 2 1 l n ∣ 1 + y 2 ∣ R = ∫ 1 + y 3 y 2 + y − 1 = ∫ 1 + y 3 y 2 d y + ∫ 1 + y 3 y − 1 d y ∫ 1 + y 3 y 2 d y = 3 1 l n ( 1 + y 3 ) y 3 + 1 = ( y + 1 ) ( y 2 − y + 1 ) ∫ 1 + y 3 y − 1 d y = ∫ y 2 − y + 1 a y + b + y + 1 c d y a + c = 0 , b − c + a = 0 , b + c = 1 , a = − c , b = 2 c c = 1 / 3 , b = 2 / 3 , a = − 1 / 3 ∫ 1 + y 3 y − 1 d y = ∫ y 2 − y + 1 ( − 1 / 3 ) y + 2 / 3 + y + 1 1 / 3 d y = − 3 1 ∫ y 2 − y + 1 y − 2 d y + 3 1 ∫ y + 1 1 d y = − 3 2 ∫ y 2 − y + 1 y − 2 1 − 2 3 d y + 3 1 l n ∣ y + 1 ∣ ∫ y 2 − y + 1 y − 2 1 − 2 3 d y = ∫ y 2 − y + 1 y − 2 1 d y − 2 3 ∫ y 2 − y + 1 1 d y = 2 1 l n ( y 2 − y + 1 ) − 2 3 ∫ y 2 − y + 1 1 d y ∫ y 2 − y + 1 1 d y = ∫ t a n 2 x + 1 − t a n x 1 s e c 2 x d x = ∫ s e c 2 x − t a n x s e c 2 x d x = ∫ c o s 2 x 1 − c o s x s i n x c o s 2 x 1 d x = ∫ 1 − c o s x s i n x 1 d x = ∫ 2 − s i n 2 x 2 d x y 2 − y + 1 1 = c 1 + ( a y + b ) 2 ( a y + b ) ′ = a 2 y 2 + 2 a b y + b 2 + 1 a c a / c = 1 , 2 b / c = − 1 , ( b 2 + 1 ) / a c = 1 , a = c = − 2 b ( b 2 + 1 ) = ( 4 b 2 ) , 3 b 2 = 1 , b = ± 3 1 b = − 3 1 , a = c = 3 2 y 2 − y + 1 1 = 3 2 1 + ( 3 2 y − 3 1 ) 2 3 2 ∫ y 2 − y + 1 1 d y = 3 2 ∫ 1 + ( 3 2 y − 3 1 ) 2 3 2 d y = 3 2 a r c t a n ( 3 2 y − 3 1 ) R = ∫ 1 + y 3 y 2 + y − 1 d y = 3 1 l n ( 1 + y 3 ) − 3 2 ( 2 1 l n ( y 2 − y + 1 ) − 3 a r c t a n ( 3 2 y − 3 1 ) ) + 3 1 l n ( y + 1 ) R = 3 2 l n ( y + 1 ) + 3 2 a r c t a n ( 3 2 y − 1 ) ∴ Q = a r c t a n ( y ) − 2 1 ∫ 1 + y 2 1 + y d y + 2 1 ∫ 1 + y 3 y 2 + y − 1 d y = a r c t a n ( y ) − 2 1 ( a r c t a n ( y ) + 2 1 l n ∣ 1 + y 2 ∣ ) + 2 1 ( ∫ 1 + y 3 y 2 + y − 1 d y ) = 2 1 x − 4 1 l n ∣ 1 + t a n 2 x ∣ + 2 1 R = 2 1 x − 4 1 l n ∣ 1 + t a n 2 x ∣ + 3 1 l n ∣ 1 + t a n x ∣ + 3 1 a r c t a n ( 3 2 t a n x − 1 )
이렇게라도 해봤는데… 답이 안나옴…
답은 pi/4 라고 하니, 알아서 도전바람…
끈기 있게 다시 시도…
∫ s i n 3 x c o s 3 x + s i n 3 x d x = ∫ t a n 3 x 1 + t a n 3 x d x , ( x = t a n − 1 y , d x = 1 1 + y 2 d y ) = ∫ y 3 1 + y 3 1 1 + y 2 d y = ∫ y 3 ( 1 + y 2 ) ( 1 + y 3 ) d y = ∫ y 3 ( 1 + y ) ( 1 + y 2 ) ( 1 − y + y 2 ) d y a y + 1 + b y + c y 2 + 1 + d y + e y 2 − y + 1 = ( a + b ) y 2 + ( b + c ) y + ( a + c ) y 3 + y 2 + y + 1 + d y + e y 2 − y + 1 y 4 ( a + b + d ) = 0 , y 3 ( b + c − a − b + e + d = 1 ) , y 2 ( a + c − b − c + a + b + e + d ) = 0 , y ( − a − c + b + c + e + d ) = 0 , a + c + e = 0 a + c + e = 0 , − a + b + e + d = 0 , 2 a + e + d = 0 , − a + c + d + e = 1 , a + b + d = 0 b + d = − a , − 2 a + e = 0 , e = 2 a , c = − 3 a , d = − 4 a , − a − 3 a − 4 a + 2 a = 1 a = − 1 / 6 , c = 1 / 2 , e = − 1 / 3 , d = 2 / 3 , b = − 1 / 2 Q = ∫ − 1 / 6 y + 1 + ( − 1 / 2 ) y + ( 1 / 2 ) y 2 + 1 + ( 2 / 3 ) y + ( − 1 / 3 ) y 2 − y + 1 d y = − 1 6 l n ( y + 1 ) − 1 2 ∫ y − 1 y 2 + 1 d y + 1 3 ∫ 2 y − 1 y 2 − y + 1 d y = − 1 6 l n ( y + 1 ) − 1 2 ∫ y y 2 + 1 d y + 1 2 ∫ 1 y 2 + 1 d y + 1 3 l n ( y 2 − y + 1 ) = − 1 6 l n ( y + 1 ) − 1 4 l n ( y 2 + 1 ) + 1 2 a r c t a n ( y ) + 1 3 l n ( y 2 − y + 1 ) x= 0 to pi/2 , y=0 to inf. y=tan(x) = 1 2 x + 1 12 ( 4 l n ( y 2 − y + 1 ) − 2 l n ( y + 1 ) − 3 l n ( y 2 + 1 ) ) = 1 2 x + 1 12 l n ( ( y 2 − y + 1 ) 4 ( y + 1 ) 2 ( y 2 + 1 ) 3 ) ( x = 0 , t h e n Q = 0 ) ( x = π / 2 , t h e n Q = π / 4 , ( lim y → ∞ l n O ( y 8 ) O ( y 8 ) = l n 1 = 0 ) ) ∴ Q = π 4 Q = 1 2 x + 1 12 l n ( ( y 2 − y + 1 ) 4 ( y + 1 ) 2 ( y 2 + 1 ) 3 ) = 1 2 x + 1 12 l n ( ( 1 + t a n 2 x − t a n x ) 4 ( 1 + t a n x ) 2 ( 1 + t a n 2 x ) 3 ) = 1 2 x + 1 12 l n ( ( s e c 2 x − t a n x ) 4 ( 1 + t a n x ) 2 ( s e c x ) 6 ) = 1 2 x + 1 6 l n ( ( s e c 2 x − t a n x ) 2 ( 1 + t a n x ) ( s e c x ) 3 ) = 1 2 x + 1 3 l n ( 1 − c o s x s i n x c o s 2 x ) − 1 6 l n ( c o s x + s i n x c o s 4 x ) = 1 2 x + 1 3 l n ( 1 − c o s x s i n x ) − 2 3 l n ( c o s x ) − 1 6 l n ( c o s x + s i n x ) + 2 3 l n ( c o s x ) = 1 2 x + 1 3 l n ( 1 − c o s x s i n x ) − 1 6 l n ( c o s x + s i n x ) + C
\begin{aligned}
&\int \frac{sin^3x}{cos^3x+sin^3x} dx \\
&=\int \frac{tan^3x}{1+tan^3x}dx, \quad (x=tan^{-1}y, dx=\frac{1}{1+y^2}dy)\\
&=\int \frac{y^3}{1+y^3}\frac{1}{1+y^2}dy \\
&=\int \frac{y^3}{(1+y^2)(1+y^3)}dy =\int \frac{y^3}{(1+y)(1+y^2)(1-y+y^2)}dy\\
&\frac{a}{y+1}+\frac{by+c}{y^2+1}+\frac{dy+e}{y^2-y+1}=\frac{ (a+b)y^2+(b+c)y+(a+c) }{y^3+y^2+y+1}+\frac{dy+e}{y^2-y+1}\\
&y^4( a+b +d)=0, y^3(b+c-a-b+e+d=1), y^2(a+c-b-c+a+b+e+d)=0,\\
&y(-a-c+b+c+e+d)=0, a+c+e=0\\
&a+c+e=0, -a+b+e+d=0, 2a+e+d=0, -a+c+d+e=1, a+b+d=0\\
&b+d=-a, -2a+e=0, e=2a, c=-3a, d=-4a, -a-3a-4a+2a=1\\
&a=-1/6, c=1/2, e=-1/3, d=2/3, b=-1/2\\
&Q=\int \frac{-1/6}{y+1}+\frac{(-1/2)y+(1/2)}{y^2+1}+\frac{(2/3)y+(-1/3)}{y^2-y+1} dy\\
&=-\frac 1 6 ln(y+1)- \frac 1 2 \int \frac{y-1}{y^2+1}dy+\frac 1 3 \int \frac{2y-1}{y^2-y+1} dy\\
&=-\frac 1 6 ln(y+1)- \frac 1 2 \int \frac y {y^2+1}dy +\frac 1 2 \int \frac 1 {y^2+1}dy+\frac 1 3 ln(y^2-y+1) \\
&=-\frac 1 6 ln(y+1)-\frac 1 4 ln(y^2+1)+\frac 1 2 arctan(y)+\frac 1 3 ln(y^2-y+1) \\
&\text{x= 0 to pi/2 , y=0 to inf. y=tan(x)}\\
&=\frac 1 2 x +\frac 1 {12} ( 4ln(y^2-y+1)-2ln(y+1)-3ln(y^2+1) )\\
&=\frac 1 2 x +\frac 1 {12} ln ( \frac{ (y^2-y+1)^4}{(y+1)^2(y^2+1)^3} ) \\
& (x=0, then Q=0 ) \\
& (x=\pi/2, then Q= \pi/4 , ( \lim_{y\to\infty} ln \frac{O(y^8)}{O(y^8)}=ln1=0) )\\
& \therefore Q=\frac {\pi}{4}\\
&Q=\frac 1 2 x +\frac 1 {12} ln ( \frac{ (y^2-y+1)^4} {(y+1)^2(y^2+1)^3} )\\
&=\frac 1 2 x +\frac 1 {12} ln( \frac{(1+tan^2x-tanx)^4}{(1+tanx)^2(1+tan^2x)^3})\\
&=\frac 1 2 x +\frac 1 {12} ln( \frac{(sec^2x-tanx)^4}{(1+tanx)^2(secx)^6})\\
&=\frac 1 2 x +\frac 1 {6} ln( \frac{(sec^2x-tanx)^2}{(1+tanx)(secx)^3})\\
&=\frac 1 2 x +\frac 1 {3} ln(\frac{1-cosxsinx}{cos^2x})-\frac 1 6 ln(\frac{cosx+sinx}{cos^4x})\\
&=\frac 1 2 x + \frac 1 3 ln(1-cosxsinx)-\frac 2 3ln(cosx)-\frac 1 6 ln(cosx+sinx)+\frac 2 3 ln(cosx)\\
&=\frac 1 2 x +\frac 1 3 ln(1-cosxsinx)-\frac 1 6 ln(cosx+sinx)+C\\
\end{aligned}
∫ c o s 3 x + s i n 3 x s i n 3 x d x = ∫ 1 + t a n 3 x t a n 3 x d x , ( x = t a n − 1 y , d x = 1 + y 2 1 d y ) = ∫ 1 + y 3 y 3 1 + y 2 1 d y = ∫ ( 1 + y 2 ) ( 1 + y 3 ) y 3 d y = ∫ ( 1 + y ) ( 1 + y 2 ) ( 1 − y + y 2 ) y 3 d y y + 1 a + y 2 + 1 b y + c + y 2 − y + 1 d y + e = y 3 + y 2 + y + 1 ( a + b ) y 2 + ( b + c ) y + ( a + c ) + y 2 − y + 1 d y + e y 4 ( a + b + d ) = 0 , y 3 ( b + c − a − b + e + d = 1 ) , y 2 ( a + c − b − c + a + b + e + d ) = 0 , y ( − a − c + b + c + e + d ) = 0 , a + c + e = 0 a + c + e = 0 , − a + b + e + d = 0 , 2 a + e + d = 0 , − a + c + d + e = 1 , a + b + d = 0 b + d = − a , − 2 a + e = 0 , e = 2 a , c = − 3 a , d = − 4 a , − a − 3 a − 4 a + 2 a = 1 a = − 1 / 6 , c = 1 / 2 , e = − 1 / 3 , d = 2 / 3 , b = − 1 / 2 Q = ∫ y + 1 − 1 / 6 + y 2 + 1 ( − 1 / 2 ) y + ( 1 / 2 ) + y 2 − y + 1 ( 2 / 3 ) y + ( − 1 / 3 ) d y = − 6 1 l n ( y + 1 ) − 2 1 ∫ y 2 + 1 y − 1 d y + 3 1 ∫ y 2 − y + 1 2 y − 1 d y = − 6 1 l n ( y + 1 ) − 2 1 ∫ y 2 + 1 y d y + 2 1 ∫ y 2 + 1 1 d y + 3 1 l n ( y 2 − y + 1 ) = − 6 1 l n ( y + 1 ) − 4 1 l n ( y 2 + 1 ) + 2 1 a r c t a n ( y ) + 3 1 l n ( y 2 − y + 1 ) x= 0 to pi/2 , y=0 to inf. y=tan(x) = 2 1 x + 1 2 1 ( 4 l n ( y 2 − y + 1 ) − 2 l n ( y + 1 ) − 3 l n ( y 2 + 1 ) ) = 2 1 x + 1 2 1 l n ( ( y + 1 ) 2 ( y 2 + 1 ) 3 ( y 2 − y + 1 ) 4 ) ( x = 0 , t h e n Q = 0 ) ( x = π / 2 , t h e n Q = π / 4 , ( y → ∞ lim l n O ( y 8 ) O ( y 8 ) = l n 1 = 0 ) ) ∴ Q = 4 π Q = 2 1 x + 1 2 1 l n ( ( y + 1 ) 2 ( y 2 + 1 ) 3 ( y 2 − y + 1 ) 4 ) = 2 1 x + 1 2 1 l n ( ( 1 + t a n x ) 2 ( 1 + t a n 2 x ) 3 ( 1 + t a n 2 x − t a n x ) 4 ) = 2 1 x + 1 2 1 l n ( ( 1 + t a n x ) 2 ( s e c x ) 6 ( s e c 2 x − t a n x ) 4 ) = 2 1 x + 6 1 l n ( ( 1 + t a n x ) ( s e c x ) 3 ( s e c 2 x − t a n x ) 2 ) = 2 1 x + 3 1 l n ( c o s 2 x 1 − c o s x s i n x ) − 6 1 l n ( c o s 4 x c o s x + s i n x ) = 2 1 x + 3 1 l n ( 1 − c o s x s i n x ) − 3 2 l n ( c o s x ) − 6 1 l n ( c o s x + s i n x ) + 3 2 l n ( c o s x ) = 2 1 x + 3 1 l n ( 1 − c o s x s i n x ) − 6 1 l n ( c o s x + s i n x ) + C
https://math.stackexchange.com/questions/198083/int-frac-sin3x-sin3x-cos3x
Author: crazyj7@gmail.com